AQAT: The Architecture Quality Assurance Tool for Critical Embedded Systems - Johnsen, Andreas; Lundqvist, Kristina; Hanninen, Kaj; Pettersson, Paul (Proceedings - International Symposium on Software Reliability Engineering, 2017)
Architectural engineering of embedded systems comprehensively affects both the development processes and the abilities of the systems. Verification of architectural engineering is consequently essential in the development of safety- and missioncritical embedded system to avoid costly and hazardous faults. In this paper, we present the Architecture Quality Assurance Tool (AQAT), an application program developed to provide a holistic, formal, and automatic verification process for architectural engineering of critical embedded systems. AQAT includes architectural model checking, model-based testing, and selective regression verification features to effectively and efficiently detect design faults, implementation faults, and faults created by maintenance modifications. Furthermore, the tool includes a feature that analyzes architectural dependencies, which in addition to providing essential information for impact analyzes of architectural design changes may be used for hazard analysis, such as the identification of potential error propagations, common cause failures, and single point failures. Overviews of both the graphical user interface and the back-end processes of AQAT are presented with a sensor-to-actuator system example.